Air-processed mixed-cation Cs0.15FA0.85PbI3 planar perovskite solar cells derived from a PbI2–CsI–FAI intermediate complex. Issue 17 (16th April 2018) - Xu, Xiuwen; Ma, Chunqing; Xie, Yue-Min; Cheng, Yuanhang; Tian, Yameng; Li, Menglin; Ma, Yuhui; Lee, Chun-Sing; Tsang, Sai-Wing
Abstract : A PbI2 –(CsI)0.15 –(FAI) x intermediate complex associated with preheating enables air-processed, high-efficiency Cs0.15 FA0.85 PbI3 PSCs for the first time. Abstract : Developing facile strategies that enable high-performance perovskite solar cell (PSC) fabrication in ambient air is appealing yet challenging for low-cost and large-scale industrial deployment. However, attempts in this regard are still limited to methylammonium lead triiodide (CH3 NH3 PbI3 ), which lags significantly behind the rapid development of the state-of-the-art formamidinium (FA) based mixed perovskites. Here, a PbI2 –(CsI)0.15 –(FAI) x intermediate complex is proposed to unlock the processing limitation and efficiently facilitate the growth of high-quality mixed-cation Cs0.15 FA0.85 PbI3 perovskite films in ambient air with relative humidity (RH) as high as 70 ± 10%. It is found that the PbI2 –(CsI)0.15 –(FAI) x ( x = 0.2 to 0.4) intermediate complex consisting of a mixture of composites is favorable for the conversion of PbI2 to high-quality Cs0.15 FA0.85 PbI3 perovskite. Eventually, it reduces the required FAI concentration deposited on the intermediate for the conversion of PbI2 to perovskite, which allows the strong hygroscopic FAI to be processed in ambient air. With the PbI2 –(CsI)0.15 –(FAI)0.3 intermediate complex, a low-temperature air-processed planar Cs0.15 FA0.85 PbI3 PSC achieves a champion power conversion efficiency (PCE) of 15.56% with superior thermal-stability and photo-durability, demonstrating its great potential for the large scale development of PSCs.